THE IMPACT OF UNEMPLOYEMENT RATE, HUMAN DEVELOPMENT INDEX, AND POPULATION ON POVERTY IN GROBOGAN REGENCY : A MULTIPLE LINEAR REGRESSION APPROACH - Dwi Wulandari (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2026)
Poverty is one of the major challenges faced by nearly all cities and regencies in Indonesia, including Grobogan Regency, Central Java. According to data released by the Central Statistics Agency (BPS) of Central Java Province, as of March 2025 the poverty rate in Grobogan stood at 10.63%, which is higher than both the provincial and national averages. Poverty is a multidimensional issue that cannot be viewed solely from an economic perspective. This study aims to analyze the effect of the Open Unemployment Rate (OUR), the Human Development Index (HDI) and population size on the poverty rate in Grobogan Regency, Central Java. The study employs secondary data obtained from BPS Grobogan Regency. The analytical method used in multiple linear regression, with three independent variables (HDI, OUR, and population size) and one dependent variable (poverty rate). The findings reveal that the Human Development Index (HDI) and population size have a significant partial effect on the poverty rate in Grobogan Regency. In contrast, the Open Unemployment Rate (OUR) does not exhibit a significant partial effect. Specifically, a 1% increase in OUR is associated with a 2.8% rise in the poverty rate, while a 1% decrease in HDI corresponds to a 9% increase in the poverty rate. Meanwhile, a 1% increase in population size leads to a 0.0002578% increase in the poverty rate. Based on these results, policy interventions should prioritize enhancing the Human Development Index while simultaneously implementing population control measures.